Anglicisms in the Canarian Regional Digital Press: An Analysis of the Newspaper La Provincia - Luján-García, Carmen (2021)
A number of studies have documented the remarkable presence of Anglicisms in various areas of Spanish speakers’ daily life. This paper reports, with updated data, the penetration of English through the digital press. The presence of English has been examined in the digital edition of Canarian newspaper La Provincia (Spain) during the first term of 2019 aiming at showing how any reader and speaker is daily exposed to Anglicisms. The method, based on the manual reading and extraction of Anglicisms in all the sections of the newspaper, reveals that the most frequently used kind of Anglicism is the non-adapted one. Furthermore, using said method, the spelling markers and, finally, the functions of these Anglicisms in the analyzed press are discussed.